Prokrastinasi Akademik Mahasiswa Ditinjau dari Keaktifan Berorganisasi - Ramanda, Peni; Sukirno, Agus; Riski, Riski (Universitas Mathla'ul Anwar Banten, 2022)
STUDENT ACADEMIC PROCRASTINATION IN TERMS OF ORGANIZATIONAL ACTIVITY. This study aims: 1) To describe the level of academic procrastination of students who follow the organization carried out by BKI FADA UIN Banten students. 2) Describe the level of academic procrastination of students who do not participate in the organization conducted by BKI FADA UIN Banten students. 3) Describe whether there is a difference between students who join the organization and students who do not join the organization conducted by BKI FADA UIN Banten students. In this study, the researcher used a comparative quantitative method where the researcher compared two variables, whether there were differences in academic procrastination between students who joined the organization and students who did not join the organization. Based on the research conducted, it can be concluded that; 1) The level of procrastination in students who do not join the organization is in the low category with an average score of 81.4. 2) The level of academic procrastination of students who join the organization is in the high category with an average value of 92.4. 3) There is a significant difference between students who do not join the organization and students who join the organization. Judging from the results of data processing in the SPSS For Windows Release version 26 program, the Sig (2-tailed) value is 0.000, which means that there is a difference between the two variables.